Clothing comfort for the dependent elderly: caregivers perspective - Caldas, Artemisia (2018)
The discussions around aging provide ideas to explore new solutions for the problems related to the elderly’s quality of life. This research includes a study about clothing and accessories design and production needs for this growing niche of the world’s population. It presents part of the collected results to develop more ergonomic clothing, with special consideration on the ergonomic, thermo physiological and sensorial comfort variables. In particularly, the elderly population dependent of care was the main target of this study. A survey was applied to the caregivers in the cities of Guimaraes (Portugal) and Teresina (Brazil) to better understand their needs and the impact garments and accessories have in their daily tasks. The main goal of this study was to elaborate more comfortable clothing, emphasizing the flexibility, softness, adaptability and adjustability to this changing body.